2015
DOI: 10.1111/ibi.12262
|View full text |Cite
|
Sign up to set email alerts
|

Wing shape and migration in shorebirds: a comparative study

Abstract: Migration is an energetically expensive and hazardous stage of the annual cycle of non‐resident avian species, and requires certain morphological adaptations. Wing shape is one of the morphological traits that is expected to be evolutionarily shaped by migration. Aerodynamic theory predicts that long‐distance migrants should have more pointed wings with distal primaries relatively longer than proximal primaries, an arrangement that minimizes induced drag and wing inertia, but this prediction has mostly been te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 51 publications
4
37
0
Order By: Relevance
“…Empirically, elongated wings have often been associated with behaviors requiring low cost flight strategies such as migration. For example, in shorebirds (Minias et al 2015) found a negative relationship between migration distance and wing roundedness, a result also consistent with passerines (Marchetti et al 1995;Outlaw 2011). On the opposite, shorter rounded wings generally enhance maneuverability during flight and are often associated with greater predator escape ability (Norberg and Rayner 1987;Betts and Wootton 1988;Srygley and Chai 1990;Fernández et al 2007).…”
Section: Wing Morphology and Microhabitatsupporting
confidence: 71%
See 1 more Smart Citation
“…Empirically, elongated wings have often been associated with behaviors requiring low cost flight strategies such as migration. For example, in shorebirds (Minias et al 2015) found a negative relationship between migration distance and wing roundedness, a result also consistent with passerines (Marchetti et al 1995;Outlaw 2011). On the opposite, shorter rounded wings generally enhance maneuverability during flight and are often associated with greater predator escape ability (Norberg and Rayner 1987;Betts and Wootton 1988;Srygley and Chai 1990;Fernández et al 2007).…”
Section: Wing Morphology and Microhabitatsupporting
confidence: 71%
“…For example, in shorebirds (Minias et al. ) found a negative relationship between migration distance and wing roundedness, a result also consistent with passerines (Marchetti et al. ; Outlaw ).…”
Section: Discussionmentioning
confidence: 56%
“…Despite being sedentary, the Azores Snipe does not show differences in the shape of the wing when compared with their migratory relatives. Although wing pointedness is correlated with migratory distance in shorebirds (Minias et al 2015), other selective pressures such as predation (Burns & Ydenberg 2002) or social selection (Fernandez & Lank 2007) may also influence wing shape. Because Snipe perform aerial displays during courtship, regardless of their migratory habits, it is possible that social selection is impeding modifications in the wing.…”
Section: Discussionmentioning
confidence: 99%
“…Irrespective of the migration strategy adopted by each species (jumps vs. hops), longer total migration distance requires not only higher energy input, but is also associated with more profound physiological and morphological adjustments (Piersma, 1998). Both fat load and total migration distance have been demonstrated to correlate with several morphological and physiological adaptations to migration in shorebirds, such as haemoglobin concentration (Minias, Kaczmarek, Włodarczyk, & Janiszewski, 2013) and wing shape (Minias, Meissner, et al, 2015).…”
Section: Migratory Traitsmentioning
confidence: 99%